2022
DOI: 10.48550/arxiv.2202.03225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-correlation functions for odd Langevin systems

Abstract: We investigate the statistical properties of fluctuations in active systems that are governed by non-symmetric responses. Both an underdamped Langevin system with an odd resistance tensor and an overdamped Langevin system with an odd elastic tensor are studied. For a system in thermal equilibrium, the time-correlation functions should satisfy time-reversal symmetry and the anti-symmetric parts of the correlation functions should vanish. For the odd Langevin systems, however, we find that the anti-symmetric par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Here we are particularly interested in the physics of soft and biological matter, in which two variational principles are mostly relevant: the principle of minimum free energy for static problems 33,34 and Onsager's variational principle (or similar principles that extend Lagrangian variational mechanics to dissipative systems 35 ) for dynamic problems. 29,31,[36][37][38][39][40] The former principle is of our particular interests in this work and is most relevant to active elastic solids.…”
Section: Variational Methods For Active Matter Staticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we are particularly interested in the physics of soft and biological matter, in which two variational principles are mostly relevant: the principle of minimum free energy for static problems 33,34 and Onsager's variational principle (or similar principles that extend Lagrangian variational mechanics to dissipative systems 35 ) for dynamic problems. 29,31,[36][37][38][39][40] The former principle is of our particular interests in this work and is most relevant to active elastic solids.…”
Section: Variational Methods For Active Matter Staticsmentioning
confidence: 99%
“…However, at time scales that are smaller than the structural relaxation time (such as unbinding time of crosslinkers in cytoskeleton and characteristic time of cell migration/division/apoptosis in connective tissues), active matter is more rigid and behaves as an elastic solid. 1,6,[26][27][28] Whereas active fluids have been studied extensively, 2,4,[29][30][31] active solids have received much less attention. 1,28,32 In this work, we consider static elasticity problems in active solids.…”
Section: Introductionmentioning
confidence: 99%
“…7G-H). The interplay between nonconservative forces and noise has also been studied (269,270). In the context of the swimming hinges, it is shown that random fluctuations give rise to (on average) persistent motion (268,212).…”
Section: Topological Defectsmentioning
confidence: 99%
“…Variational methods have been widely used in the physical modeling of soft matter. These methods are mostly based on two variational principles of statistical thermodynamics: the variational principle of minimum free energy (MFEVP) for static problems [33,34] and Onsager's variational principle (OVP) for dynamic problems [31,33,36,39,63,64]. In our former work [36], we have explored the variational methods that are based on OVP for the modeling of active matter dynamics.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…By contrast, the formulation of phenomenological models is based upon symmetry consideration, conservation laws of mass, momentum, and angular momentum, and laws of Variational principles have been proposed in various fields of physics. Here we are particularly interested in the physics of soft and biological matter, in which two variational principles are mostly relevant: the principle of minimum free energy for static problems [33,34] and Onsager's variational principle (or similar principles that extend Lagrangian variational mechanics to dissipative systems [35]) for dynamic problems [29,31,[36][37][38][39][40]. The former principle is of our particular interests in this work and is most relevant to active elastic solids.…”
Section: Introductionmentioning
confidence: 99%